2007
DOI: 10.1001/jama.297.9.978
|View full text |Cite
|
Sign up to set email alerts
|

Major and Minor ECG Abnormalities in Asymptomatic Women and Risk of Cardiovascular Events and Mortality

Abstract: ESTING 12-LEAD ELECTROCARdiogram (ECG) abnormalities are independently associated with incident coronary heart disease (CHD) and cardiovascular disease (CVD) events. 1-14 Many of the prior studies included only men or compared men and women, but the women were not selected for age or the presence or absence of underlying heart disease. 1-13 Data are sparse regarding the prognostic significance of baseline ECG abnormalities in postmenopausal women without clinically manifest heart disease. 14 Furthermore, there… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
136
2
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(148 citation statements)
references
References 21 publications
7
136
2
3
Order By: Relevance
“…3 Two studies have reported on the change in the AUC. 19,20 These studies showed slight improvements in AUC, of a similar magnitude as in the current study. Yet the change in the AUC is of limited clinical usefulness.…”
Section: Comparison With Existing Literaturesupporting
confidence: 86%
See 1 more Smart Citation
“…3 Two studies have reported on the change in the AUC. 19,20 These studies showed slight improvements in AUC, of a similar magnitude as in the current study. Yet the change in the AUC is of limited clinical usefulness.…”
Section: Comparison With Existing Literaturesupporting
confidence: 86%
“…The discriminative value of both models was expressed with the area under the receiver operator curve (AUC). The 10-year absolute risk to develop e3 British Journal of General Practice, January 2015 [18][19][20] was calculated. The NRI quantifies the percentage of correct movement across categories for those with and without events.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, different studies may vary with regard to the specific ECG classification into major and minor abnormalities (25)(26)(27)(28)(29). The nomenclature of major and minor ECG abnormalities used in this study, although consistent with other publications from the CHS (30,31), does not reflect the current classification according to the Minnesota criteria (32).…”
Section: Discussionmentioning
confidence: 72%
“…Most biologic assays were performed by the Central Laboratory of Lausanne University Hospital, which is regularly checked for performance and quality. As in other studies, 10 we calculated 10-year CAD risk for each participant using the Framingham risk score. 11 This version of the Framingham risk score includes diabetes mellitus and estimates the risk for CAD (angina pectoris, recognized and unrecognized myocardial infarction, coronary insufficiency, and CAD death).…”
Section: Methodsmentioning
confidence: 99%